Ground water monitoring using KoboCollect apps in Nepal - International Maize and Wheat Improvement Center (International Maize and Wheat Improvement Center, 2024)
The video aims to develop an engaging and informative video that effectively communicates CSISA's work and impact, contributing to increased awareness, knowledge sharing, and advocacy efforts on groundwater monitoring using the Kobo Collect App. The researchers and users of the tool through CSISA Activity may find this video/tool effective.